Effects of Upper Extremity Immobilization and Use of a Spinner Knob on Vehicle Steering. (November 2017) - Jackson, Lyle T.; Crisler, Matthew C.; Tanner, Stephanie L.; Brooks, Johnell O.; Jeray, Kyle J.
Background: A person's ability to safely drive while immobilized is not well defined. Steering ability with a spinner knob during immobilization is unknown. The goal of this study is to further clarify the effect of immobilization on steering reaction time and accuracy with and without a steering wheel spinner knob.Methods: Twenty participants were enrolled in this crossover trial using a driving simulator with an automatic transmission. Five conditions were tested in a counterbalanced order. Steering reaction time and accuracy (number of errors on a dynamic steering task at 2 difficulty levels) were measured. Participants were allowed to steer with the immobilized extremity.Results: No significant differences in reaction time were observed between any conditions. Both immobilized conditions and difficulty level of the steering task led to diminished accuracy compared with controls, resulting in significantly more errors. The use of a spinner knob significantly improved the accuracy for the condition with the sugar-tong splint during the easier steering task, but this improvement was not observed in the harder steering task. There were no differences between conditions based on gender or observed use of the immobilized arm.Conclusions: Immobilization had a negative effect on steering accuracy for both the wrist splint and the sugar-tong splint condition, which may negatively impact driving ability of immobilized patients. Immobilization, regardless of spinner knob use, did not significantly impact steering reaction time. The steering wheel spinner knob did not consistently improve accuracy, and further study is needed to determine its utility.